Powrót do teorii dwóch prawd - Woleński, Jan (Filozofia Nauki, 2006)
The theory of double truth was proposed in the Middle Age by Latin Averroists as a solution of how the relation between faith (religion, theology) and reason (science) should be conceived. In general terms, according to this theory, there are two orders, one dictated by faith and second dictated by reason. Both are epistemologically different and cannot mutually remain in logical relations such as (in)consistency or entailment. This view was used in the Middle Ages for defending science against a claim that it is the ancilla thelogiae only. The author compares the theory of double truth with other solutions like the model of identity of science and theology or the model of two overlapping regions (Thomas Aquinas). It is argued that the substantial difference of the language of faith and the language of reason makes logical relations between statements of science and statements of theology impossible. In particular, all cosmological proofs of God's existence as well as projects of intelligent design fail if the theory of double truth is adopted.